Hubungan antara Kekuatan Otot Lengan terhadap Kemampuan Smash Permainan Bola Voli Pada Siswa SMK Maospati - Rohmad; Wanuh Wiyarko; Bayu Purwo Adhi (Cipta Media Harmoni, 2025)
The teacher has given the smash technique in volleyball, but during the practice of playing, SMK Maospati students still continue to experience obstacles and barriers in the process of implementing the smash movement in the placement of arm muscles when hitting the ball and height. This causes low learning outcomes of smash in volleyball. Therefore, this study is intended to determine the relationship between arm muscle strength and height to the smash method in SMK Maospati students, Magetan Regency. This type of research is descriptive quantitative with correlation analysis techniques. The subjects of this study were students at SMK Maospati, Magetan Regency with a total of 12 students in Grades X and XI. The results are that there is a strong relationship between arm muscle strength and height to the ability of volleyball smashes in SMK Maospati students, Maospati District, Magetan Regency. These results confirm that to improve smash abilities, students must also be given an approach or training that focuses on the freshness and fitness of children, especially those related to the power of volleyball smashes.